2020
DOI: 10.1186/s12913-020-05906-y
|View full text |Cite|
|
Sign up to set email alerts
|

The 2020 blast in the Port of Beirut: can the Lebanese health system “build back better”?

Abstract: The August 2020 explosion in Lebanon resulted in casualties, injuries, and a great number of internally displaced persons. The blast occurred during an economically and politically complex time in the country. Given multiple and competing post-explosion reconstruction priorities, in ths editorial we briefly examine the requirements for a build back better scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 5 publications
(4 reference statements)
2
24
0
Order By: Relevance
“…This review complements recent reports (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and further provide an in-depth analysis of the Beirut blast and its health and environmental implications, and suggests actionable recommendations and strategies.…”
Section: Introductionsupporting
confidence: 67%
“…This review complements recent reports (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and further provide an in-depth analysis of the Beirut blast and its health and environmental implications, and suggests actionable recommendations and strategies.…”
Section: Introductionsupporting
confidence: 67%
“…One reason behind this surge is that many people have been unable to follow precautionary measures, such as social distancing, during the relief efforts in Beirut. Also, some of the major hospitals have been partially or heavily damaged as a result of the huge blast at Beirut's port [ 35 , 36 ]. MoPH reported that almost all COVID-19 beds are full and hospitals are running out of space for new patients by the time of writing this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the PRE-RE-SyST model follows the assumption that disability disparities, exacerbated and made more visible during the COVID-19 pandemic, can foster greater social awareness and provide opportunities for change towards a more inclusive society, after the pandemic [ 72 , 117 ]. This assumption is aligned with the “build back better” framework which positions disasters as an opportunity to build more resilient systems, [ 118 ] as well as the more recent “build back fairer” framework, aimed at breaking cycles of inequality [ 119 , 120 ]. The latter fosters the adoption of equity-oriented approaches to population health and development toward building more resilient societies, better prepared to weather future pandemics and other emergencies (e.g.…”
Section: Discussionmentioning
confidence: 99%